Factors associated with COVID-19 vaccination intentions among adults in the deep South. Issue 6 (7th February 2022) - Daniel, Casey L.; Williams, Jacob; Legg, Rachel; McGowen, Chelsea; Stutzman, Jesse
Highlights: Less than half of respondents reported intent to receive a COVID-19 vaccine. Flu vaccine behaviors may help identify COVID-19 vaccine behaviors. Better education about COVID-19 vaccines is needed to increase uptake. Many respondents were undecided, indicating potential to increase vaccine uptake. Abstract: The recent approval of several COVID-19 vaccines signals progress toward controlling the pandemic. Although social distancing and masking have been effective, vaccines are an important additional measure of protection to reduce COVID-19 spread. Adequate uptake is essential to reach herd immunity, estimated to be approximately 67%. However, vaccine hesitancy, the fast-tracked nature of the COVID-19 vaccines, and misinformation circulating through various forms of media have contributed to lower vaccination intention than desired. The current research study developed an online survey conducted via Facebook to explore the attitudes and perceptions of adult Alabama residents about COVID-19 and the COVID-19 vaccines. Of the 3, 781 respondents, only 44.3% reported intent to receive a vaccine, with a large proportion reporting they were unsure (28.1%). Lack of intention to vaccinate was associated with low educational attainment, low COVID-19 knowledge levels, low income, and African American race. The current survey also explored participants' influenza vaccine behavior as this information can also be used to inform successful COVID-19 vaccine distribution. Of the respondents, 56% report receiving the yearly influenza vaccine and the majority receive it at a pharmacy or healthcare provider office. This informs likely successful locations for COVID-19 vaccine distribution. Appropriate education targeted to populations most likely to refuse COVID-19 vaccination is essential to promote uptake. The information collected from the current study should be utilized to inform effective and efficient vaccine distribution strategies.